DNA Methylation-Based Point-of-Care Cancer Detection: Challenges and Possibilities. Issue 11 (November 2019) - Sina, Abu Ali Ibn; Carrascosa, Laura G.; Trau, Matt
Abstract : Eukaryotic cell DNA conserves a distinct genomic methylation pattern, which acts as a molecular switch to control the transcriptional machinery of the cell. However, pathological processes can alter this methylation pattern, leading to the onset of diseases such as cancer. Recent advances in methylation analysis provide a more precise understanding of the consequence of DNA methylation changes towards cancer progression. Consequently, the discoveries of numerous methylation-based biomarkers have inspired the development of simple tests for cancer detection. In this opinion article, we systematically discuss the benefits and challenges associated with the promising methylation-based approaches and develop a point-of-care index to evaluate their potential in terms of point-of-care cancer diagnostics. Highlights: DNA methylation has long been regarded as a hallmark of cancer and hold great promises for early-stage cancer detection. Recent years have seen tremendous advancement in methylation-based cancer biomarker discovery and many technologies have been developed to detect these biomarkers. DNA methylation-based technologies have high potential in point-of-care cancer diagnostics. A point-of-care index (POCi) could identify the challenges and possibilities of current methylation-based cancer detection techniques.